Corporate Vicarious Liability in the Crime of Participating in Bribery in Indonesia - Yusof Ferdinan Wangania; Supot Rattanapun (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
The complexity of the corporate landscape has positioned enterprises as key actors in criminal offenses, including bribery. Although the National Criminal Code (Law No. 1/2023) recognizes corporations as subjects of criminal law, the application of vicarious liability in corporate bribery cases remains underexplored. This study examines the implementation of vicarious liability for corporations in the context of bribery in Indonesia, particularly after the enactment of the National Criminal Code. Utilizing a juridical-normative methodology and statutory and conceptual approaches, this research analyzes primary and secondary legal materials qualitatively and descriptively. The findings reveal that the National Criminal Code incorporates the concepts of identification and vicarious liability into corporate accountability, extending the scope to include those in de facto control of the organization. Applying vicarious liability in bribery cases requires proof of a causal link between the bribery act and the corporation's interests. This study contributes to the alignment of vicarious liability with established principles of criminal law and provides insights into corporate accountability under the new Criminal Code framework.